Penggunaan Platform Merdeka Mengajar (PMM) Untuk Meningkatkan Kompetensi Guru Di Sekolah Dasar - Mai Sri Lena; Sahrun Nisa; Ola Kurnia Putri; Rizka Hidayatul Husna (Pusat Riset dan Inovasi Nasional, 2023)
The Independent Teaching Platform (PMM) is a technology platform that accommodates teachers to obtain references, inspiration and understanding of the independent curriculum. This platform also helps teachers to develop their own creativity, because the learning features on the Independent Platform provide independent training facilities with unlimited access. This study aims to analyze the use of the Independent Teaching Platform (PMM) in increasing teacher competence in elementary schools. This type of research uses descriptive qualitative research with data collection techniques through questionnaires indirectly through the Google form. The research results showed that the benefits of the Independent Platform were felt by 90.5% of teachers in West Sumatra played a role in increasing the competence of teachers in elementary schools.